Utilization of e-NAM Facilities and Services by Farmers in Telangana - Malliboina Mahesh Yadav; A. Sakeer Husain; Lokesh Srinivasaiah (Indian Journal of Extension Education, 2022)
The study was undertaken to know the e-NAM usage pattern of farmers in Hyderabad and Warangal Districts of Telangana, India, in 2019-20. The utilization index was constructed based on the responses received from the respondents for statements related to utilization patterns. The Pearson correlation method was used to measure the relationship between the profile characters of the respondents and the utilization index. More than 50 per cent of the farmers in the study were imitators and more than 60 per cent of respondents belonged to the medium category in information seeking behavior. e-NAM facilities viz., checking price (70%), mobile number linkage for the information (53%) were the most used facilities by the respondents. Education and Awareness factors significantly contributed to the utilization pattern of e-NAM resources.